2021
DOI: 10.2174/2589977513666210226123920
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Green Synthesized Metallic Nanoparticles Against Staphylococcus aureus

Abstract: Background: The recent treatment challenges posed by the widespread emergence of pathogenic Multidrug‐Resistant (MDR) bacterial strains are a cause of huge health troubles worldwide. Infections caused by MDR organisms are associated with longer period of hospitalization, increased mortality, and inflated healthcare costs. Staphylococcus aureus is one of these MDR organisms identified as an urgent threat to human health by the World Health Organization. Infections caused by S. aureus may range from simple cutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 120 publications
0
9
0
Order By: Relevance
“…Green synthesis of nanoparticles must be considered as the preferred technique for plant treatment, due to its several advantages over chemical-based methods. In addition, to low toxicity levels, due to their affordability, green-synthesized NPs are easily scaled up for bulk production [ 36 ]. Although there are several kinds of green synthesis methods, the use of plant extracts is a common and the most preferred method, since plants are easily accessible and less toxic than microbes [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Green synthesis of nanoparticles must be considered as the preferred technique for plant treatment, due to its several advantages over chemical-based methods. In addition, to low toxicity levels, due to their affordability, green-synthesized NPs are easily scaled up for bulk production [ 36 ]. Although there are several kinds of green synthesis methods, the use of plant extracts is a common and the most preferred method, since plants are easily accessible and less toxic than microbes [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…[36,37] All these properties of copper oxide increase dramatically when it is manufactured on a nanoscale. [38] In fact, due to high surface area to volume ratio copper oxide nanoparticles (CuONPs), have unique physical, chemical, and biological properties when compared to its bulk. [39] Numerous studies have been carried out on the green synthesis of CuONPs with plant extracts such as Coffea arabica, Camellia sinensis, Costus Pictus leaf extract and Juglans nigra leaf extracts.…”
Section: Introductionmentioning
confidence: 99%
“…[ 36,37 ] All these properties of copper oxide increase dramatically when it is manufactured on a nanoscale. [ 38 ] In fact, due to high surface area to volume ratio copper oxide nanoparticles (CuONPs), have unique physical, chemical, and biological properties when compared to its bulk. [ 39 ]…”
Section: Introductionmentioning
confidence: 99%
“…Several studies report the use of plant extracts for the synthesis of AgNPs with significant antimicrobial activity. leaf extracts of moringa oleifera , [ 42 ] Green tea extract, [ 43 ] Salvia spinosa leaf extracts, [ 44 ] leaf extract of gymnema sylvestre , [ 45 ] leaf and root extract of berberis vulgaris , [ 46 ] Cassia toral root extracts, [ 47 ] sesame oil cake, [ 48 ] Phyla dulcis , [ 49 ] scutellaria barbata extract, [ 50 ] kalanchoe pinnata leaf extract, [ 17 ] vaccinium arctostaphlyos fruit extract , [ 51 ] glycosmis pentaphylla fruit extract, [ 52 ] extracts of Ilex paraguariensis , [ 53 ] and leaf extract of cissus quadarangularis . [ 54 ] In this report, the biomolecules present in the plant extract serve as reducing and/or capping agents in reaction with silver nitrate, a commonly used precursor in the synthesis of silver nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Thus nanotherapeutics is one of the approaches that have been studied for the development of effective drugs against various bacterial infections. [17] Several studies have shown that nanotherapeutic agents have a faster onset of action in terms of their therapeutic effect, and also minimize side effects by reducing the daily doses required for a therapeutic effect. [18] Nanotechnology is the science of atomic, molecular, and supramolecular molecules, aimed at creating nanostructures with enhanced functionality, [19] and the term "nanoparticle" describes a particular matter ranging in size from 1 to 100 nm.…”
Section: Introductionmentioning
confidence: 99%